2001
DOI: 10.1093/nar/29.11.2217
|View full text |Cite
|
Sign up to set email alerts
|

DNA synthesis fidelity by the reverse transcriptase of the yeast retrotransposon Ty1

Abstract: The fidelity of the yeast retrotransposon Ty1 reverse transcriptase (RT) was determined by an assay based on gel electrophoresis. Steady-state kinetics analyses of deoxyribonucleotide (dNTP) incorporation at a defined primer-template site indicate that Ty1 RT misincorporates dNTP at a frequency of 0.45 x 10(-5) for the A(t):A mispair in which dATP is misincorporated opposite a template A to 6.27 x 10(-5) for the C(t):A mispair. The G(t):G and T(t):T mispairs are formed with very low efficiency. The fidelity pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 26 publications
2
26
0
Order By: Relevance
“…The observed mutation rate of 2.5 × 10 −5 bp per cycle suggested that Ty1 mutated as rapidly as retroviruses. The in vitro study involved steady state kinetics of misinsertion opposite A, T, G and C residues at defined primer-template sites (Boutabout et al, 2001). Ty1 RT was found to be less error prone than lentiviral RTs such as HIV-1, HIV-2 and EIAV and comparable to that of oncoretroviral RTs such as AMV.…”
Section: Saccharomyces Cerevisiae Ty1mentioning
confidence: 99%
“…The observed mutation rate of 2.5 × 10 −5 bp per cycle suggested that Ty1 mutated as rapidly as retroviruses. The in vitro study involved steady state kinetics of misinsertion opposite A, T, G and C residues at defined primer-template sites (Boutabout et al, 2001). Ty1 RT was found to be less error prone than lentiviral RTs such as HIV-1, HIV-2 and EIAV and comparable to that of oncoretroviral RTs such as AMV.…”
Section: Saccharomyces Cerevisiae Ty1mentioning
confidence: 99%
“…These elements are believed to have diverged early in the evolution of LTR retrotransposons, well before retroviruses. Therefore, it is likely that the mechanism of self-priming represents an early form of initiating RTN in LTR retroelements (16), as it was advantageous for these retroelements to use a tRNA-independent mechanism of priming cDNA synthesis.The only RTs from LTR retrotransposons extensively studied in vitro were those of Ty1 and Ty3 that belong to different retrotransposon groups, the Pseudoviridae and the Metaviridae, respectively (4,8,23,24). We have recently expressed in bacteria an enzymatically active Tf1 RT and studied its basic biochemical properties (14).…”
mentioning
confidence: 99%
“…The only RTs from LTR retrotransposons extensively studied in vitro were those of Ty1 and Ty3 that belong to different retrotransposon groups, the Pseudoviridae and the Metaviridae, respectively (4,8,23,24). We have recently expressed in bacteria an enzymatically active Tf1 RT and studied its basic biochemical properties (14).…”
mentioning
confidence: 99%
“…In support of vertical radiation, pairwise comparisons of Tvv1 lTrs indicate that their pattern of similarity matches the successive divergence of the asterids and rosids followed by that of the clades within the rosids and the species within Solanum. nevertheless, the analysis may be biased by possible differing degrees of transpositional activity in the various species and clades, because for retrotransposons the error rates for replication via reverse transcription and as integral chromosomal components differ greatly (Gabriel et al 1996;Boutabout et al 2001;Abram et al 2010).…”
Section: Discussionmentioning
confidence: 99%